2017
DOI: 10.1016/j.sjbs.2015.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water-deficit stress and paclobutrazol on growth, relative water content, electrolyte leakage, proline content and some antioxidant changes in Curcuma alismatifolia Gagnep. cv. Chiang Mai Pink

Abstract: Effects of water-deficit stress and paclobutrazol (PBZ) on the physiological and biochemical changes in Curcuma alismatifolia Gagnep. cv. Chiang Mai Pink (Zingiberaceae) were investigated. One hundred rhizomes were grown for 30–35 days and then divided into the following 4 treatments: (1) well-watered, (2) not watered, (3) well-watered and treated with 1500 ppm PBZ being applied once to the soil, and (4) not watered but treated with 1500 ppm PBZ. After 50 days of growth, watering was withheld for 30 days. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
54
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 33 publications
9
54
0
1
Order By: Relevance
“…The PBZ application lowered the MDA contents in leaves and roots of quinoa under salt stress observed in the present study, which also corresponds with the finding that triazole compounds improve salinity tolerance due to lower ROS accumulation or increased pool of osmolytes (Figure c) to reduce lipid peroxidation by the oxidative stress. Such improvement in salinity tolerance by exogenously applied PBZ in quinoa plants had also been reported in rice (Pan et al., ), tomato (Tuna, ) and tulips (Jungklang, Saengnil, & Uthaibutra, ) under different abiotic stresses. This was also confirmed by a strong positive correlation between roots and leaves for osmoprotectants, lipid peroxidation and antioxidant enzymes (Figure ).…”
Section: Discussionsupporting
confidence: 61%
“…The PBZ application lowered the MDA contents in leaves and roots of quinoa under salt stress observed in the present study, which also corresponds with the finding that triazole compounds improve salinity tolerance due to lower ROS accumulation or increased pool of osmolytes (Figure c) to reduce lipid peroxidation by the oxidative stress. Such improvement in salinity tolerance by exogenously applied PBZ in quinoa plants had also been reported in rice (Pan et al., ), tomato (Tuna, ) and tulips (Jungklang, Saengnil, & Uthaibutra, ) under different abiotic stresses. This was also confirmed by a strong positive correlation between roots and leaves for osmoprotectants, lipid peroxidation and antioxidant enzymes (Figure ).…”
Section: Discussionsupporting
confidence: 61%
“…In the present experiment, cassava experienced drought at five months after planting for three months prior to harvest. Jugklang and Saengnil (2012) reported that PBZ application to the crops increased drought tolerance by inducing a number of physiological and biochemical adaptation such as maintaining relative water content in leaves, decreasing electrolyte leakage and proline content, increasing the vitamin C and vitamin E levels and the activities of catalase and superoxide dismutase (Jungklang et al 2017). Based on these results, PBZ might delay leaves senescence during drought period and finally allow that plant to maintain its leaf number per plant and leaf area index in the present experiment.…”
Section: Results and Discussion Plant Heightmentioning
confidence: 99%
“…Proline accumulation is an indicator of the plant's response to abiotic stresses, especially drought and salinity. Some studies report that proline accumulation is lower in tolerant plants than in plants that are sensitive to salinity stress and drought (Jungklang et al, 2017). Proline is a compound that includes amino acids that can be used to show the plant's response to stress in drought and salinity (Li et al, 2018).…”
Section: Discussionmentioning
confidence: 99%